2010
DOI: 10.1080/02640410903428525
|View full text |Cite
|
Sign up to set email alerts
|

Application of four different football match analysis systems: A comparative study

Abstract: Using a video-based time-motion analysis system, a semi-automatic multiple-camera system, and two commercially available GPS systems (GPS-1; 5 Hz and GPS-2; 1 Hz), we compared activity pattern and fatigue development in the same football match. Twenty football players competing in the Spanish second and third divisions participated in the study. Total distance covered during the match for the four systems was as follows: 10.83 + or - 0.77 km (semi-automatic multiple-camera system, n = 20), 9.51 + or - 0.74 km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
174
4
27

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(210 citation statements)
references
References 21 publications
5
174
4
27
Order By: Relevance
“…The use of technologies such as Global Positioning System (GPS) devices and semi-automated camera systems are now relatively commonplace within men's soccer. These technologies are more time efficient than the traditional video-based time motion analysis systems and offer greater objectivity and volume of information [4]. Furthermore, more detailed evaluations of specific elements of a player's physical performance as opposed to generic time-motion analysis can be undertaken [5][6][7][8].…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations
“…The use of technologies such as Global Positioning System (GPS) devices and semi-automated camera systems are now relatively commonplace within men's soccer. These technologies are more time efficient than the traditional video-based time motion analysis systems and offer greater objectivity and volume of information [4]. Furthermore, more detailed evaluations of specific elements of a player's physical performance as opposed to generic time-motion analysis can be undertaken [5][6][7][8].…”
Section: )mentioning
confidence: 99%
“…More recent studies [10][11][12][13] , using larger sample sizes (n = 13 -58) have reported an increase in total distance covered (~10 km) for national team players when measured using video-tape and GPS technology. Whilst a trend exists for an increase in total distance covered compared to early reports, these differences may also to some extent reflect differences in data collection methods [4]. Total distance covered provides a global estimation of physical match-play but it is high-speed running which is deemed to be more informative and reflective of the game [5,7].…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…This multiple-camera system passively tracks the movements of every player using a sampling rate of 10.0 Hz over the entire course of matches. The workings, accuracy and reliability of the AMISCO Pro ® system in measuring player movements in elite soccer competition have been described in detail elsewhere [6,26] [3]. Data on the overall distance covered and that run in high-intensity activity respectively were collected for each half of games.…”
Section: Match Performance Data Collection Procedures and Measuresmentioning
confidence: 99%